Development Monitoring Information System Based on Website and Whatsapp Gateway at Sd Telkom Makassar - Al Imran; M. Syahid Nur Wahid; Fadhlirrahman Baso; A. Fadil (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
The research aims to determine the results of developing a monitoring system based on a website and WhatsApp gateway at SD Telkom Makassar, as well as to evaluate the system's performance using ISO/IEC 25010 standards. This research uses the Research and Development (R&D) approach. The development model applied is the prototype model. Data was collected through interviews and questionnaires. The system was implemented with several technologies, including the Laravel framework, MySQL, and WhatsApp gateway. The system testing used ISO/IEC 25010, covering 8 aspects: (1) Functional suitability aspect fulfilled 134 out of 134 total features, scoring 100% and categorized as suitable. (2) The Usability aspect achieved a percentage score of 96.3%, classified as very good. (3) The Performance efficiency aspect received a grade of B with a performance percentage of 82%. (4) Reliability aspect achieved a metric score of 100%. (5) The Maintainability aspect met the criteria of instrumentation, consistency, and simplicity. (6) The Portability aspect achieved a perfect score with no errors. (7) Compatibility aspect scored well with no errors. (8) The Security aspect was at Vulnerability Level 0 (safe). The developed system successfully met the ISO/IEC 25010 testing standards, this qualifying as a reliable information system